The Influence of Marketing Mix on the Decision to Purchase Bakpia at Pia Warung Glenmore Jember Branch in Jember Regency - Anggraeni, Oktanita Jaya; Kurniawati, Dewi; Sundari, Sri; Hudori, Huda Ahmad (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
Pia Warung Glenmore Jember Branch is one of the Bakpia companies that is currently facing business competition. This research was conducted to test and analyze the influence of the marketing mix on the decision to purchase bakpia at Pia Warung Glenmore Jember Branch. The population in this study were consumers who purchased Glenmore bakpia with a sample of 70 respondents. The analytical tool used is multiple linear analysis with the help of IBM SPSS 21 software. The results of this research can be concluded that the product, price, promotion and distribution channel variables jointly have a significant influence on the decision to purchase bakpia at Pia Warung Glenmore Jember Branch. Partially, the results of this research can be concluded that product variables and distribution channels have a significant effect on purchasing decisions, while price and promotion variables have a partially insignificant effect on purchasing decisions. Based on the results of the analysis, the product variable is the variable that has a dominant influence on the decision to purchase bakpia at Pia Warung Glenmore Jember Branch in Jember Regency.